Effect of Calcium and Potassium on Antioxidant System of Vicia faba L. Under Cadmium Stress - Siddiqui, Manzer H. (Molecular Diversity Preservation International (MDPI), 2012)
Cadmium (Cd) in soil poses a major threat to plant growth and productivity. In the present experiment, we studied the effect of calcium (Ca(2+)) and/or potassium (K(+)) on the antioxidant system, accumulation of proline (Pro), malondialdehyde (MDA), and content of photosynthetic pigments, cadmium (Cd) and nutrients, i.e., Ca(2+) and K(+) in leaf of Vicia faba L. (cv. TARA) under Cd stress. Plants grown in the presence of Cd exhibited reduced growth traits [root length (RL) plant(−1), shoot length (SL) plant(−1), root fresh weight (RFW) plant(−1), shoot fresh weight (SFW) plant(−1), root dry weight (RDW) plant(−1) and shoot dry weight (SDW) plant(−1)] and concentration of Ca(2+), K(+), Chlorophyll (Chl) a and Chl b content, except content of MDA, Cd and (Pro). The antioxidant enzymes [peroxidase (POD) and superoxide dismutase (SOD)] slightly increased as compared to control under Cd stress. However, a significant improvement was observed in all growth traits and content of Ca(2+), K(+), Chl a, Chl b, Pro and activity of antioxidant enzymes catalase (CAT), POD and SOD in plants subjected to Ca(2+) and/or K(+). The maximum alleviating effect was recorded in the plants grown in medium containing Ca(2+) and K(+) together. This study indicates that the application of Ca(2+) and/or K(+) had a significant and synergistic effect on plant growth. Also, application of Ca(2+) and/or K(+) was highly effective against the toxicity of Cd by improving activity of antioxidant enzymes and solute that led to the enhanced plant growth of faba bean plants.